Characterization of blanched and unblanched powdered alupidan (Tetrastigma harmandii) leaves as souring agent. - Baui, Joemel Escaner
Alupidan (Tetratstigma harmandii)is among the wildly growing plants traditionally used for its sourness. This study aimed to develop Alupidan leaves powdered in order to put science into the traditional knowledge on its use and promote its value as a souring agent. The powdered Alupidan leaves (PAL) was prepared: Treatment 1 (T1) was blanched and Treatment 2 (T2) was Air-dried. Both treatments were dried at 65 °C ± 5°C until a moisture content below 10% dry basis. The fresh Alupidan leaves has a pH of 4.10, MC (dry basis) of 86.9, TA (as oxalic acid) of 1.60, and Aw of 0.897. Blanched PAL had a pH of 4.06, MC (dry basis) of 3.99, TA (as oxalic acid) of 5.24 and Aw of 0.424. Air-dried PAL had pH of 3.81, MC (dry basis)of 34.3, TA (as oxalic acid) of 3.53, and Aw of 0.418. Based on its qualities, PAL has a potential competitive value as powdered souring agent. The 30% (w/v) concentration of the blanched PAL in sour preparation was preferred. Sourness intensity of both treatments was "moderately sour", however, blanched PAL was evaluated to have a colour of "extremely dark green" while air-dried PAL was "very dark green". Two sample T-test at P 0.05 showed a significant difference in the pH, %MC, and %TA between T1 and T2. However, no significant difference in sourness intensity was perceived between the treatments. The sourness intensity of Alupidan leaf powder was affected by the method of drying; however, the blanched leaves were more preferred by the panel. Both the blanched and air-dried PAL has similar sourness intensity with the fresh Alupidan leaves at 30% (g/mL) water concentration.